1997
DOI: 10.1093/milmed/162.5.346
|View full text |Cite
|
Sign up to set email alerts
|

Urogenital War Injuries

Abstract: Out of 1,350 war casualties treated at the University Hospital Rebro during the defensive war in Croatia, 60 (4.4%) injuries of the urogenital tract were present. Among these 60 casualties, 51 (85.0%) had multiple injuries, most often abdominal and urogenital. These patients were accordingly treated by combined urological and surgical teams. Regarding injuries, there were 21 kidney injuries, 11 ureter (2 patients had bilateral injuries), 7 urinary bladder, 2 urethral, 15 testicular, and 6 penile injuries subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Tucak et al documented GU trauma as 2.5% of all casualties while renal injuries as the major organ afflicted was 45% during the war, however they managed to salvage kidneys in 75% of the cases 2 . Marekovic et al studied war injuries during Croatian war and documented incidence of GU injuries as 4.4% of total casualties; renal trauma was 35% and was the commonest of all; 6 out 21 (28.6%) underwent nephrectomy due to high grade renal injuries 16 . Abu-Zidan et al during the Gulf war documented 42% of renal injuries with 33% nephrectomy 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Tucak et al documented GU trauma as 2.5% of all casualties while renal injuries as the major organ afflicted was 45% during the war, however they managed to salvage kidneys in 75% of the cases 2 . Marekovic et al studied war injuries during Croatian war and documented incidence of GU injuries as 4.4% of total casualties; renal trauma was 35% and was the commonest of all; 6 out 21 (28.6%) underwent nephrectomy due to high grade renal injuries 16 . Abu-Zidan et al during the Gulf war documented 42% of renal injuries with 33% nephrectomy 17 .…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9] Several reviews have been published on the experience with urologic injuries in the Croatian war. [10][11][12][13] Vuckovic et al [13] demonstrated that renal and ureteral injuries constituted 47% of the war injuries, and injuries of the bladder, urethra, and external genitalia occurred in 17.2%, 4.6%, and 30.8%, respectively. The University Hospital at Rebro reported that 1350 war casualties were treated with a 4.4% incidence of urologic injuries; these included 35% to the kidney, 15% ureter, 11.6% bladder, 3.3% urethra, 25% testes, and 10% penis.…”
Section: Discussionmentioning
confidence: 99%
“…The University Hospital at Rebro reported that 1350 war casualties were treated with a 4.4% incidence of urologic injuries; these included 35% to the kidney, 15% ureter, 11.6% bladder, 3.3% urethra, 25% testes, and 10% penis. [ 10 ] In a review of war injuries to the ureter in Croatia, another institution found a 2.6% incidence of urologic injury among 4425 wounded patients, of which 9.5% involved the ureters. [ 12 ] Our rates of ureteral injury were found to be higher with %17.3.…”
Section: Discussionmentioning
confidence: 99%
“…Although injuries to the external genitalia are typically not in and of themselves life threatening, they are commonly associated with other potentially life-threatening injuries (for example, to abdomen, pelvis or groin) [2]. Traumatic injuries to the genitourinary tract are seen in 2.2-10.3% of patients admitted to hospitals [3], [4], [5]. Of these injuries, between one-third and two-thirds of cases are associated with injuries to the external genitalia [3].…”
Section: Introductionmentioning
confidence: 99%